Genetic variability of lemon basil (Ocimum × africanum Lour.) from Indonesian archipelago based on morphological and inter-simple sequence repeats markers (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Makmur K, Chikmawati T, Sobir. 2020. Genetic variability of lemon basil (Ocimum × africanum Lour.) from Indonesia based on morphological characters and ISSR markers. Biodiversitas 21: 5948-5953. Lemon basil (Ocimum × africanum Lour.) or kemangi is a highly beneficial plant, yet still underutilized. Therefore, providing necessary information on genetic diversity of this species is essential for further utilization. The aim of this study was to elucidate genetic diversity of 33 accessions of O. × africanum collected from four Islands of Indonesia along with three accessions of Ocimum basilicum L. Morphological observation was conducted on 37 morphological characters following the International Union for the Protection of New Varieties of Plants descriptor guidelines; subsequently, 13 ISSR primers were employed in molecular analysis. Both morphological and molecular data were analyzed based on simple matching similarity index using UPGMA method. Morphologically, O. × africanum and O. basilicum were clearly separated at the similarity index of 0.52, and among two species were divided into two groups according to two either character. ISSR analysis using 13 ISSR primers produced 111 DNA bands, and 108 of them (97.29%) were polymorphic. Cluster analysis based on ISSR data could not explicitly separate O. × africanum and O. basilicum accessions. Besides, Ocimum accessions collected from the same area did not always cluster into one group.
Keywords: Lemon basil, genetic diversity, ISSR, morphology, Ocimum × africanum